Pengaruh Gaya Kepemimpinan Transformasional, Kualitas Kehidupan Kerja Dan Motivasi Kerja Terhadap Kinerja (Studi Kasus Di Polres Batu) - Aulia Sukma Rachmawati; Budi Wahono; Ety Saraswati (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study was conducted to determine the effect of transformational leadership style, quality of work life and work motivation on  performance (a case study on employees at the Batu Police). This research uses explanatory research and quantitative approach. The sample in this study included 75 respondent at the Batu PoliceTo solve the problem in this research, using validity test, reliability test, normality test, multiple linear regression test, multicollinearity test, heteroscedasticity test, classic assumption test. This study uses multiple linear regression analysis with the help of SPSS 20. The results of this study are simultaneously the variable Effect of Transformational Leadership Style, Quality of Work Life and Work Motivation on Employee Performance at the Batu Police, the variable Transformational Leadership Style partially has a positive and significant effect on employee performance in Batu Police, the variable of Quality of Work Life partially has a positive and significant effect on Performance at the Batu Police, the variable of Work Motivation partially has a positive and significant effect on Performance at the Batu Police Keywords: Performance, Transformational Leadership Style, Quality of Work Life, Work Motivation